OPTIMISING PALLIATIVE CARE FOR FRAIL ELDERS IN COMMUNITY SETTINGS; PREFERENCES FOR CARE AND PALLIATIVE OUTCOMES IN THE LAST MONTHS OF LIFE. Issue 1 (1st March 2014) - Evans, CJ; Bone, A; Morgan, M; McCrone, P; Gaoi, W; Wright, J; Hall, S; Gomes, B; Gordon, E; Lindsey, F; Bruni, C; Taherzadeh, S; et al.
Abstract : Introduction: People are living longer and increasingly die with frailty and complex co-morbidities. Many suffer unnecessarily because of limited recognition of palliative care needs, aggressive management and under treatment. Palliative care is advocated for frail older people with non-malignant conditions to improve assessment and treatment, but with little evidence of effectiveness. Aim(s) and method(s): Aim to determine the preferences for care and palliative outcomes for frail elders by place of death (own home, care home or hospital). Post-bereavement survey (QUALYcare) to carers (n=882) of people aged over 75 years or over via ONS. Survey examines quality of EoLC, preferences and palliative care outcomes for frail elders (malignant and non-malignant conditions). Data analysis using descriptive and inferential statistics to compare by place of death frequency of attainment of preferred place of death, prevalence of palliative outcomes, and formal and informal service use (no. and %, with 95% CI, Chi2 ) Results: 443 (50.2%) participants mainly a son/daughter (68.2%). Majority deceased widowed (53.5%) and lived alone (41.8%). Most resided last months at home (42.9%), or care home (nursing home 22.8%; residential 12%). 35.7% died in hospital, mostly transferring from own home ()n=74/190) or a residential home (n=25/53), but few from nursing homes (15/101). Nearly half who died in hospital resided there for 1–4 weeks (45.6%). Conclusion(s): An opportunity to improve palliative care is responsiveness to timely discharge from hospital for people to die in preferred community settings. Nursing homes care for the majority of people until death, but residential care homes with no onsite nursing require greater support.